Photobiomodulation preconditioning for oral mucositis prevention and quality of life improvement in chemotherapy patients: a randomized clinical trial - Marwa Khalil; Omar Hamadah; Maher Saifo (BMC Oral Health)
Abstract Background Given the suffering experienced by cancer patients, effective solutions must be found to prevent painful and debilitating side effects of anti-cancer treatment. This trial aims to study the effect of preconditioning with photobiomodulation in preventing oral mucositis and xerostomia in cancer patients undergoing chemotherapy alone for the first time, and to examine its role in improving patients’ quality of life. Materials and methods This is a prospective, randomized, double-blind clinical trial including 45 patients divided into three age- and sex-matched groups. Group 1 received basic oral care instructions before undergoing chemotherapy. Group 2 received basic oral care instructions plus photobiomodulation using an intraoral 650 nm diode laser. Group 3 received basic oral care instructions plus photobiomodulation using a 650 nm diode laser intraorally and a 980 nm diode laser extraorally. Results After one week of follow-up, 73.3% of patients in Group 2 and 80% in Group 3 did not develop oral mucositis. The remaining patients in both groups experienced only mild erythema. In contrast, all patients in Group 1 developed oral mucositis, ranging from mild erythema to ulceration greater than 3 cm². After two weeks of follow-up, 80% of patients in Group 2 and 86.7% in Group 3 remained free of oral mucositis. The remaining patients in both groups experienced only mild erythema. In contrast, 93.3% of patients in Group 1 developed oral mucositis, with cases ranging from mild erythema to ulcers larger than 3 cm². There were statistically significant differences between the three groups in oral mucositis assessment scale after one week and after two weeks (p < 0.001). Specifically, ulcerative mucositis was not observed in both laser groups, while it was observed in 13.3% of patients in Group 1. However, these differences were not statistically significant (p = 0.129). Regarding Late Effects in Normal Tissue (LENT-SOMA) scale, there was a statistically significant difference between the three groups studied (p = 0.037). There was also a statistically significant difference in the Oral Health Impact Profile (OHIP-14) between the three groups studied (p = 0.003 after one week, p = 0.023 after two weeks). Conclusion Preconditioning before starting chemotherapy, whether with the intraoral red laser alone or in combination with the extraoral infrared laser, has shown significant results in preventing oral mucositis and dry mouth, and it has also played a major role in improving patients’ quality of life. Trial registration This trial was registered in ISRCTN registry under no ISRCTN70634383 ( https://doi.org/10.1186/ISRCTN70634383 ) on 24/07/2023.